2005
DOI: 10.1038/sj.ijir.3901387
|View full text |Cite
|
Sign up to set email alerts
|

Peak systolic velocity in patients with arterial erectile dysfunction and peripheral arterial disease

Abstract: The aim of this study is to evaluate whether penile peak systolic velocity (PSV) varies in patients with erectile dysfunction (ED) due to artery insufficiency associated with abnormalities in other arterial districts or not. To accomplish this, cavernous artery PSV was determined 10, 20 and 30 min after intracavernously administering alprostadil by means of echo-color Doppler to a total of 65 consecutive patients (age range 52-78 years). In all, 18 patients had ED alone (group A) and served as controls, 15 had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
2
10
0
1
Order By: Relevance
“…Men with ED and both carotid and lower limb abnormalities had the most severe penile artery disease based on ultrasound assessments of all three vascular beds. 30 Both of these studies support the concept that many men with vascular ED should be regarded as having generalized vascular atherosclerosis. Additional evaluation of the carotid and lower limb peripheral vascular beds may help to identify men who, after presenting with ED as their initial clinical symptom, would benefit from additional diagnostic testing and/or aggressive pharmacologic intervention for risk factor management.…”
Section: Erectile Dysfunction As a Harbinger Of Cvd Kl Billups Et Alsupporting
confidence: 66%
“…Men with ED and both carotid and lower limb abnormalities had the most severe penile artery disease based on ultrasound assessments of all three vascular beds. 30 Both of these studies support the concept that many men with vascular ED should be regarded as having generalized vascular atherosclerosis. Additional evaluation of the carotid and lower limb peripheral vascular beds may help to identify men who, after presenting with ED as their initial clinical symptom, would benefit from additional diagnostic testing and/or aggressive pharmacologic intervention for risk factor management.…”
Section: Erectile Dysfunction As a Harbinger Of Cvd Kl Billups Et Alsupporting
confidence: 66%
“…The authors did not describe clinical methods for LEAD diagnosis, and did not control for blood pressure. In the other two studies [12, 13], the authors reported that narrowing of the larger lower extremity arteries (based on Doppler ultrasound) was more common in men with ED, and that men with lower extremity arterial narrowing and ED had significantly worse penile arterial insufficiency; they did not report small-vessel LEAD or control for any covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Little attention has been paid to the association between ED and LEAD, although they share common cardiovascular risk factors including age, diabetes, hypertension, dyslipidemia, sedentary lifestyle, obesity, alcohol use, and smoking [46], as well as endothelial dysfunction [7] and inflammation [810]. None of the three studies that have reported the association between ED and LEAD have specifically addressed the independent ED association with small-vessel LEAD [1113]. …”
Section: Introductionmentioning
confidence: 99%
“…18,19 While previous studies have shown an association between PSV of cavernous arteries and either carotid or femoral IMT, [20][21][22] there are no reports linking PSV measures to global atherosclerotic burden. This study uses a score that incorporates IMT measurements and the presence and size of plaques from both the carotid and femoral arteries to assesses the presence of a correlation between the extent of penile vascular disease and the global atherosclerotic burden.…”
mentioning
confidence: 98%